Landscape stereotypes and potential of creative economic narratives in the tourism marketing of Lake Constance as a destination - Lara Leuschen; Tatjana Thimm (Via@)
The Lake Constance region is due to its scenic attractiveness one of the most visited destinations in German-speaking countries. Scenic attractiveness as well as so-called landscape stereotypes also play a decisive role in tourism marketing. Tour operators reproduce supra-individual landscape concepts and establish mental geographies that ultimately influence the choice of destinations. A growing trend in tourism is the emergence of creative narratives in tourism marketing and tourism offers induced by creative companies. By means of a discourse-analytical investigation, whose theoretical and conceptual frame of reference is the hegemony and discourse theory of Laclau and Mouffe (1985), recurring landscape stereotypes are identified in tourist promotional material for the destination Bodensee. Based on these results as well as expert interviews with regional tourism stakeholders, a discussion of the creative economic potential for regional tourism marketing will take place. The investigation shows that these potentials are currently not being exhausted. At the same time, creative tourism can help a rural region, such as Lake Constance, to position itself as an alternative to city tourism, while at the same time addressing the lucrative target group 60plus.